Pengaruh Ukuran Perusahaan, Leverage, Ukuran Dewan Komisaris Terhadap Pengungkapan CSR dengan Moderasi Profitabilitas - Mukti, Lailatul Latifa; Bahri, Syaiful; Isnaini, Nurdiana Fitri (BISMA : Business and Management Journal, 2025)
Corporate Social Responsibility (CSR) is a form of corporate responsibility that encompasses social, economic, and environmental aspects. CSR reporting is based on the Triple Bottom Line concept, which emphasizes that a company's operations should not only be profit-oriented but also have a positive impact on the environment and surrounding community. This study aims to analyze the influence of company size, leverage, and board of commissioners size on Corporate Social Responsibility (CSR) disclosure, as well as the moderating role of profitability in this relationship. The methods used in this study include multiple regression analysis with a t-test for testing the main hypothesis, as well as Moderated Regression Analysis (MRA) to test the influence of moderating variables. The research sample consists of 15 non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2022–2024. The results of the study indicate that leverage and board of commissioners size significantly influence CSR disclosure, while company size does not influence CSR disclosure. Additionally, profitability can only moderate the relationship between leverage and CSR disclosure, but cannot moderate the relationship between company size or board of commissioners size and CSR disclosure.